Vehicle routing problem analysis with environmental considerations (AACINI - International Journal of Industrial Engineering, 2021)
Green logistics seeks to minimize the environmental impact generated by multiple logistics activities. To achieve this goal, this paper is based on a Pollution Routing Problem (PRP) model, which determines the best routes for a set of vehicles to serve a group of clients. By including fuel consumption in the analysis, this model can reduce fleet emissions.Then, a PRP variant is introduced and developed. This new model helps determining the optimal fleet size by including the fixed cost of the fleet under analysis – including maintenance cost, leasing, among others –.The routes generated with both models are compared with those generated by a traditional Vehicle Routing Problem (VRP) through a case study of real characteristics. As a result, significant reductions in fuel consumption – reaching 17 % – as well as slight decreases in total routes costs – close to 4% – are generated by both PRP models. However, PRP models slightly increase the total time required by the routes – 0,3 % on average –.
Keywords: Routing models; Green logistics; Pollution; Fuel consumption; Fleet sizing